2015
DOI: 10.1002/pssa.201532380
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mobility and stability in organic thin film transistors consisting of bilayer gate dielectrics

Abstract: One of the important problems in organic thin film transistors (OTFTs) is the existence of traps on oxide gate dielectrics which degrades the device performance and stability. By modifying the dielectric oxide surface, we obtained devices with bilayer dielectrics that show high mobility and good operational stability compared with the devices based on bare silicon dioxide dielectric layer. The average carrier mobility increases from 0.19 (without surface modification) to 0.35, 0.51, and 0.97 cm2 V−1 s−1 after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For the preparation of FETs and FET‐based sensors, the active layer is usually fabricated by thermal evaporation methods. Pentacene is one of the commonly used thermally evaporated semiconductors for electronics and sensors due to its relatively high mobility as well as its stability . Yakuphanoglu et al demonstrated a flexible photodetector by employing thermally evaporated pentacene as the sensor's active material .…”
Section: Approaches To Fabricate Flexible Sensorsmentioning
confidence: 99%
“…For the preparation of FETs and FET‐based sensors, the active layer is usually fabricated by thermal evaporation methods. Pentacene is one of the commonly used thermally evaporated semiconductors for electronics and sensors due to its relatively high mobility as well as its stability . Yakuphanoglu et al demonstrated a flexible photodetector by employing thermally evaporated pentacene as the sensor's active material .…”
Section: Approaches To Fabricate Flexible Sensorsmentioning
confidence: 99%
“…Sun et al [98] have shown that the life-time of OTFTs can be improved by using a bilayer gate dielectric. The low-k polymer used above the SiO 2 layer in this structure reduces the hydroxyl groups at the surface and makes the structure impervious to moisture.…”
Section: High-k/low-k Bilayer-based Otftsmentioning
confidence: 99%
“…The threshold voltage ( V th ) was extracted from the plot of square root of drain voltage (| I DS | 1/2 ) versus gate voltage ( V GS ) and determined as the intercept at I DS = 0. The dielectric constant (κ) of REO films, estimated thicknesses of PS, HMDS, and ODPA layers on Si, saturated mobility (μ), and subthreshold swing (SS) of OTFTs are calculated using the following equations: where C i is the capacitance of the gate dielectric per unit area, A is the contact area of Si/Ln 2 O 3 /Au capacitor, κ is the dielectric constant, d is the thickness of Ln 2 O 3 films, W is the channel width, L is the channel length, I DS is the drain current, V GS is the gate voltage, and V th is the threshold voltage. , …”
Section: Methodsmentioning
confidence: 66%
“…As depicted in Figure a–c, ultrasmooth surfaces can be observed for Ln 2 O 3 (Ln = La, Gd, and Er) films after postannealing treatment. Specifically, the root-mean-square (rms) roughnesses are 0.09, 0.10, and 0.08 nm for Ln = La, Gd, and Er, respectively, which are comparable to those of commercially available thermally grown SiO 2 dielectric layer . In addition, the pristine ultrasmooth surface provides a good contact with top electrodes in capacitors or the semiconductor layers in transistors.…”
Section: Resultsmentioning
confidence: 99%